An intriguing window opened by a metallic two-dimensional Lindqvist-cobaltporphyrin organic framework as an electrochemical catalyst for the CO2 reduction reaction. Issue 29 (20th July 2020) - Wang, Cong; Zhu, Chang-Yan; Zhang, Min; Geng, Yun; Li, Yang-Guang; Su, Zhong-Min
Abstract : 2D Co–PMOF, through the integration of electron-rich reductive Lindqvist-type POMs with cobaltporphyrins, exhibits superior electrocatalytic activity for CO2 reduction to CH4 due to the low theoretical driven potential (0.41 V). Abstract : Adequate studies have confirmed that polyoxometalates (POMs) are preeminent multi-electron donors and metalloporphyrins are electrochemically generated active catalysts for the CO2 reduction reaction. Integrating electron-rich POMs with metalloporphyrins in a metallic and stable organic framework can create facile and fascinating heterogeneous electrochemical catalysts by merging their complementary advantages and extensive promising possibilities. Herein, we designed and screened a series of stable and metallic two-dimensional (2D) polyoxometalate–metalloporphyrin organic frameworks (TM–PMOFs, TM in porphyrin = Fe, Co, Ni, Cu, Zn, Ru, Rh, Pd, Os, Ir, or Pt) constructed by linking reductive Lindqvist-type hexamolybdate ([Mo6 ] 2e/2H ) with 4-connected tetra-(4-aminophenyl) metalloporphyrin (TM-TAPP) building structs through the MoN triple bond, whose CO2 electrochemical reduction performances and processes are studied in detail by means of density functional theory (DFT). Our computations reveal that the Lindqvist-type clusters [Mo6 ] 2e/2H act as multi-electron regulators for the reduction reaction, and then the most promising catalyst for the reduction from CO2 to CH4 has the lowest theoretical driven potential (0.41 V). Moreover, the [Mo6 ] 2e/2H units inside are easily reduced from the [Mo6 ] with a driven potential (0.08 V). Our work will encourage more experimental studies to further explore metallic 2D PMOF materials for CO2 electrochemical reduction.